Salute e disuguaglianze in Europa Processi sociali e meccanismi individuali in azione - Mascagni, Giulia (Strumenti per la didattica e la ricerca, 2010)
This work analyses the relation between social inequality and health by focusing on the social processes and individual mechanisms that construct it within the area of action of the economic sphere, the cultural sphere and the social and territorial sphere. Within this framework, the body is conceived as a link between the physical, biological and material dimensions and the social, relational and emotional dimensions. At the same time, the proposal is to go beyond the well-known relationship between economic resources/social position and levels of health/life expectation, concentrating on the specific social and psychological dynamics generated by the availability of socio-economic capital. The over-simplified perspective of the social gradient of health is overtaken by an analysis of the relational dimension of the individual and his/her reference groups, and finally by appraising both the individual and collective aspects that can be traced to the social and political context and to the different welfare systems.